B cell-targeting chimeric antigen receptor T cells as an emerging therapy in neuroimmunological diseases - Haghikia, Aiden; Schett, Georg; Mougiakakos, Dimitrios (Lancet Neurology, 2024)
Background: Neuroimmunology research and development has been marked by substantial advances, particularly in the treatment of neuroimmunological diseases, such as multiple sclerosis, myasthenia gravis, neuromyelitis optica spectrum disorders, and myelin oligodendrocyte glycoprotein antibody disease. With more than 20 drugs approved for multiple sclerosis alone, treatment has become more personalised. The approval of disease-modifying therapies, particularly those targeting B cells, has highlighted the role of immunotherapeutic interventions in the management of these diseases. Despite these successes, challenges remain, particularly for patients who do not respond to conventional therapies, underscoring the need for innovative approaches. Recent developments: The approval of monoclonal antibodies, such as ocrelizumab and ofatumumab, which target CD20, and inebilizumab, which targets CD19, for the treatment of various neuroimmunological diseases reflects progress in the understanding and management of B-cell activity. However, the limitations of these therapies in halting disease progression or activity in patients with multiple sclerosis or neuromyelitis optica spectrum disorders have prompted the exploration of cell-based therapies, particularly chimeric antigen receptor (CAR) T cells. Initially successful in the treatment of B cell-derived malignancies, CAR T cells offer a novel therapeutic mechanism by directly targeting and eliminating B cells, potentially overcoming the shortcomings of antibody-mediated B cell depletion. Where next?: The use of CAR T cells in autoimmune diseases and B cell-driven neuroimmunological diseases shows promise as a targeted and durable option. CAR T cells act autonomously, penetrating deep tissue and effectively depleting B cells, especially in the CNS. Although the therapeutic potential of CAR T cells is substantial, their application faces hurdles such as complex logistics and management of therapy-associated toxic effects. Ongoing and upcoming clinical trials will be crucial in determining the safety, efficacy, and applicability of CAR T cells. As research progresses, CAR T cell therapy has the potential to transform treatment for patients with neuroimmunological diseases. It could offer extended periods of remission and a new standard in the management of autoimmune and neuroimmunological disorders.
CRIS-Team Scopus Importer:2024-05-24